Corneal Clarity and Visual Outcomes after Small-Incision Lenticule Extraction and Comparison to Femtosecond Laser-Assisted In Situ Keratomileusis. (15th March 2017) - Lazaridis, Apostolos; Droutsas, Konstantinos; Sekundo, Walter; Petrak, Michael; Schulze, Stephan
Abstract : Purpose . To evaluate corneal clarity and visual outcomes after small-incision lenticule extraction (SMILE) and compare them to femtosecond laser-assisted in situ keratomileusis (FS-LASIK). Materials and Methods . Fifty-eight myopic eyes of 33 patients who underwent SMILE were compared to 58 eyes of 33 patients treated with FS-LASIK. All procedures were performed using VisuMax® femtosecond laser and MEL 80® excimer laser (Carl Zeiss Meditec AG, Germany). Pentacam™ (Oculus, Germany) was used for pre- and 3-month postoperative corneal densitometry (CD) analysis. CD was evaluated at 3 optically relevant, concentric radial zones (0–2 mm, 2–6 mm, and 0–6 mm annulus) around the corneal apex and at 3 different anatomical corneal layers (anterior, central, and posterior). Associations of postoperative CD values with the lenticule thickness and ablation depth were examined. Preoperative and postoperative corrected distance visual acuity (CDVA) values were also compared. Results . After SMILE, the total CD (all corneal layers) at 0–6 mm annulus showed no significant change compared to preoperative values (P = 0.259 ). After FS-LASIK, the total CD was significantly reduced (P = 0.033 ). Three-month postoperative CD showed no significant differences between the 2 groups for all examined annuli (0–2 mm: P = 0.569 ; 2–6 mm: P = 0.055 ; and 0–6 mm: P = 0.686 ). Total CD after SMILE at 0–6 mm annulus displayed a weak negative association with the lenticule thickness (P = 0.079, R 2 = 0.0532 ) and after FS-LASIK displayed a weak negative association with the ablation depth (P = 0.731, R 2 = 0.0015 ). Postoperative CDVA was similar for both groups (P = 0.517 ). Conclusion . Quantification of corneal clarity using the Scheimpflug CD showed similar results before and 3 months after SMILE. Compared to FS-LASIK, no significant differences of corneal clarity and CDVA were found 3 months postoperatively.